Pengembangan Model Kemitraan Sekolah Dengan Orang Tua Melalui Media Sosial Dalam Peningkatan Mutu Berbasis Sekolah di Sekolah Menengah Swasta - Krismanda, Mutia Ayu; Ismanto, Bambang; Iriani, Ade (Universitas Kristen Satya Wacana, 2017)
The purpose of this research is to analyze the factual model of school partnership with parents through social media in school-based quality improvement management in SMA Kristen 1 Salatiga and result in the development of school partnership model with parents through social media in school-based quality improvement management in private high schools. It is Research and Development (R & D) research. Data collection techniques used interviews and documentation studies. The development phase is done through (1) Potential and Problem, (2) Data Collection, (3) Product Design, (4) Design Validation, and (5) Design Repair. The results showed that SMA Kristen 1 Salatiga had run the family education program quite well. Several activities in the family education program at the school has been implemented before the schools get funding from the government partnership program. Schools have also begun to seek the use of social media as a means of strengthening communication with parents and other stakeholders, but nevertheless in its development in the field of management has not been maximized. The researchers also found no model formulated by the school associated with this family education program because the new school programmed the partnership into a family education program within one year. The product of this research is a school partnership model with parents through social media at a private high school equipped with guides for the implementing parties.